2015
DOI: 10.1108/bfj-06-2014-0216
|View full text |Cite
|
Sign up to set email alerts
|

Private labels

Abstract: Purpose -In today's highly competitive consumer marketplace, developing and managing successful private label offerings has become a priority for many retailing companies. The purpose of this paper is to analyze product, retailer, and individual factors from the private label brand that influence consumers' loyalty and purchase intention; along with the influence of the manufacturer identification on the product package on purchase intention. Design/methodology/approach -A structural equation model is run on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 51 publications
1
14
0
5
Order By: Relevance
“…A literatura reporta um relacionamento direto entre imagem da marca e imagem da loja (Porter & Claycomb, 1997), e que associações e avaliações positivas da loja levarão a uma imagem de marca mais favorável (Wu et al, 2011). A imagem da loja e sua reputação melhoram a imagem da marca própria e sua qualidade percebida (Porral & Lang, 2015). Silva, Merlo, e Nagano (2012) sugerem que a imagem da loja, sua limpeza e organização, maior conhecimento e familiaridade com a loja são fatores que influenciam a disposição dos consumidores para confiar na e comprar a marca própria da loja.…”
Section: Imagem Da Loja E Marca Própriaunclassified
“…A literatura reporta um relacionamento direto entre imagem da marca e imagem da loja (Porter & Claycomb, 1997), e que associações e avaliações positivas da loja levarão a uma imagem de marca mais favorável (Wu et al, 2011). A imagem da loja e sua reputação melhoram a imagem da marca própria e sua qualidade percebida (Porral & Lang, 2015). Silva, Merlo, e Nagano (2012) sugerem que a imagem da loja, sua limpeza e organização, maior conhecimento e familiaridade com a loja são fatores que influenciam a disposição dos consumidores para confiar na e comprar a marca própria da loja.…”
Section: Imagem Da Loja E Marca Própriaunclassified
“…Porral and Lang (2015) indicated that corporate reputation and store image facilitate private label image and private label image positively influences consumers' purchase intention toward private label products indirectly through private label loyalty. Since Porral and Lang (2015) focused on Spain retailers, more research needs to be conducted in other contexts. Pina et al (2010) propose that familiarity with the parent brand has a positive effect on attitude toward the extension simply because of more exposure to the parent brand.…”
Section: Private Label Imagementioning
confidence: 99%
“…With regard to store image, service quality, price/value, convenience, and product quality are selected since they represent a typical set of hypermarket attributes (Beristain, Zorrilla 2011). Prior studies have examined the effects of store image on private label perceived quality/quality perception (Bao et al 2011;Porral, Lang 2015), private label image (Porral, Lang 2015), brand experience (Dolbec, Chebat 2013), brand attitude (Dolbec, Chebat 2013), and purchase intention (Bao et al 2011;Porral, Levy-Mangin 2016). However, Hartman and Spiro (2005) propose that store image is a necessary but insufficient construct to understand consumer behavior and store performance and suggest researchers use store knowledge, which includes both store image and store awareness.…”
Section: Store Knowledgementioning
confidence: 99%
See 2 more Smart Citations